CONSTRUCTION OF FOUNDATIONS ON DRY SOILS - Bakhromov Makhmud Mamathanovich (Journals Park Publishing, 2023)
The relevance of the topic, the importance of geological research, the importance of building pile foundations in such conditions, the characteristics of porous and saline soils, loose soils saturated with water, tasks in the construction of foundations in such complex conditions.
Keywords: soil, foundation, geology, pile foundations, porous soils, porous soils.